Kreativitas Pengajar dalam Penentuan Bahan Ajar Bahasa Mandarin untuk Peningkatan Kualitas Pembelajaran - Sutandi, Septerianie (Zenit, 2013)
In the Chinese language teaching in Indonesia, course books become one of the most prominent problems. Most of the Chinese educational institutions in Indonesia are still using Chinese course books published by China, Taiwan, Singapore and Malaysia. It is known that there are no course books that are absolutely perfect and suitable to be used by all language learners. These circumstances lead to the selection of course books which has become a complex task. The selection ofcourse books is connected with the course books evaluation, both internal and external. Good or bad quality of course books has impacts and influences to the entire teaching process .In addition, the selection of course books needs to pay attention to many aspects. Course books must be able to meetthe Indonesian social needs of the Chinese language in accordance with the educational institution’s purpose of Chinese language learning, the characteristics of learners’ age as well as learning language, and also their Chinese language proficiency level.This paper specifically describes how to improve the quality of learning, while creativity is required in selecting Chinese language course books for elementary level adult learners in Indonesia.Keywords: quality of learning, creativity, the selection of course book, elementary Chinese, Indonesian adults